Introducing an anthropology of convenience. Issue 2 (7th June 2021) - Oka, Rahul
Abstract : This article serves to introduce the Special Issue of Economic Anthropology dedicated to "Convenience as a Driver, Mediator, and Moderator of Social Economies." The twelve articles in this issue are based on papers presented at the fortieth annual meeting of the Society for Economic Anthropology at the University of Notre Dame from April 30 to May 1, 2020. In this introductory article, I briefly introduce, conceptualize, and generally define "convenience" as a heuristic and part of doxa and as a powerful force driving social economies, freshly revealed in the fractures left by the global COVID‐19 pandemic. I then discuss the etymology of the term convenience and review previous research on the topic of convenience within marketing, technology, business, and the medical sectors, which reveal it to be a fluid, multidimensional concept centered on key concepts such as efficiency, efficacy, ease, comfort, and/or advantage, but also culturally circumscribed. The articles in this issue speak to the complexities of "convenience" with ethnographic cases from the Americas, Europe, Africa, and Asia. Being one of the cornerstones of consumption driving contemporary global economies, "convenience" as a driver of economies has significant and even positive impacts for issues such as poverty alleviation. It also has, in this hyperscale global economic landscape, negative implications for human societies in its impacts on health and the environment. As such, I argue that convenience is a crucial topic for future anthropological concern.